Trends and Issues in Medication Management in Home Care for Gouty Arthritis Patients: Literature Review - Soares, Agostinha; Sari, Putri Irwanti; Maulana, Muhammad Riski Isra; Ariesti, Abella Dwi (Program Studi Keperawatan Universitas Jambi, 2024)
Introduction : Gouty arthritis is a prevalent and painful form of inflammatory arthritis, primarily managed through medication. Effective home care for gout patients hinges on proper medication management, including correct dosing, adherence, and monitoring of potential side effects. This literature review explores recent trends and challenges in medication management for gouty arthritis patients receiving home care, aiming to provide insights for improving patient outcomes. Methods: A comprehensive search of relevant studies was conducted, analyzing findings on home management of gouty arthritis patients, treatment-related barriers, and the role of healthcare providers in patient adherence. Results: indicate that although medication adherence is essential for effective management, numerous issues, such as patient misunderstanding, adverse effects, and accessibility of medications, contribute to non-adherence. Additionally, family involvement and ongoing healthcare support significantly impact patient outcomes in home care settings. Conclusion: suggest that enhancing patient education, simplifying medication regimens, and increasing support from healthcare providers can improve medication adherence and efficacy in managing gouty arthritis at home. Further research is recommended to develop targeted interventions addressing these challenges in medication management for gout patients in home care.